Once again about “Military Anarchy” - Tsirkin, J.B. (Gerión. Revista de Historia Antigua, 2011)
The “military anarchy” witnessed the decline and fall of the political institutions of the Early Empire. That period may be interpreted not only as a time of total destruction but also as a transition from on stage of the Roman state to another. The transition was rather spasmodic, revolutionary. By analogy the “military anarchy” may be defined as the second Roman Revolution, just appearing new elements of a future state: The Late Empire.
Keywords: Political changes; Autocracy; Decentralization; Ruling elite; Sacralisation